O significado de Theós em grego - Ullman, Reinholdo Aloysio (Classica - Revista Brasileira de Estudos Clássicos, 1989)
This paper deals with the Greek word "theós" in diferent levels. 1. Its etymological origin, not yet clearly elucidated; but the authors generally agree that it means "something bright". 2. "Theós" as predicative name, being used near masculine, feminine and neutral words, meaning "something beautiful" or "something terrible". 3. In Homer's work we find two significances, namely (theós) is applied to the anthropomorphical gods and to prominent persons. 4. Among the Romans, "theós" assumes the same significance as described in the preceding item. 5. Finally “theós" is studied in different Greek phliosophers, since Xenophanes, Heraclit and others, until Philon of Alexandria. The paper tries to demonstrate the effort of mankind, represented by vigorous thinkers, to find a steady foundation that justifies the human existence.